Course Scheduling System Using Genetic Algorithm - Harry Rahmat Gazali; Satria Perdana Arifin; Rika Perdana Sari (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Scheduling of courses in an university is not easy to solve. Beside viewing from the amount courses, we also need to view from lecturers perspective, namely possibilities of the lecturer that will teach more than one course. Because there is a possibility that the number of courses and the number of lecturers are not comparable. Moreover, classroom availability to manage teaching-learning activity should also be considered. Scheduling of courses at Fakultas Keguruan dan Ilmu Pendidikan Universitas Lancang Kuning still done manually, so that it requires a relatively long time in scheduling the courses and human errors often occurs in form of conflict on lecturer’s teaching schedule, classrooms usage, and the courses schedule of each classes. Therefore, a solution is needed to solve the existing scheduling problems. The method used is a Genetic Algorithm which is a computational approach to solve modeled problems by the biological evolution process. However, the use of Genetic Algorithm is still causing a conflict on the lecturers (1,70 %), usage of the classrooms (19,03 %) and the schedule of each classes (5,96 %), so these results can not be used for a real scheduling and still need researches and further development by trying different methods such as selection, crossover and mutation. Key words: Scheduling of courses, Genetic Algorithm